The Right of Access to Environmental Information in the Light of the Case C-673/13 P of 23 November 2016 — European Commission V Stichting Greenpeace Nederland - Bazylińska-Nagler, Justyna (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
In order to be able to ensure that the competent authorities take the right decisions and to participate effectively in decision-making, the public must know that the emissions were correctly or incorrectly assessed and must be thoroughly informed so as to understand how those emissions could affect the environment. The main thesis of this article is that there is a significant contradiction between environmental democracy standards in EU law and the protection of confidential commercial or industrial information. In line with the EU’s access to documents laws, information that would harm the commercial interests of a third party can not be made public if there is not an overriding public interest justifying such a disclosure.A significant part of this article has become a commentary on a very recent Court of Justice of the European Union judgment in appeal of 23rd November 2016 - European Commission v Greenpeace Nederland and Pesticide Action Network Europe. The case discused in this work addresses the fundamental issue – the right of access to environmental documents, and in particular, the scope of the concept of ‘information on emissions into the environment’. The conclusions reached by the CJEU in this judgment may have wide-ranging consequences for EU manufacturers of plant protection products and biocides. In general, this judgement may have significant and widespread implications for companies seeking to protect trade secrets and other sensitive information.
Keywords: Konwencja z Aarhus (1998); prawo dostępu do informacji o środowisku; informacje handlowe